tính bằng cách hợp lí
\(1+8.\left(3^2+1\right).\left(3^4+1\right).\left(3^8+1\right)-9^8\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
c) This makes no sense. What is quadrilateral ABCE while B, E, C are collinear? May be you mean ABCD but you make some mistake when typing.
ADCE is a parallelogram, therefore, \(CE//AD\) or \(BC//AD\)
Thus, we can easily prove that ABCD is a trapezoid.
Consider the triangle ABE, its height AH is also a median. This means ABE is an isosceles triangle, whose bisector is also AH. Thus, \(\widehat{BAH}=\widehat{EAH}\)
Clearly, we get \(\widehat{BAH}=\widehat{ECA}\left(=90^o-\widehat{B}\right)\), so, \(\widehat{EAH}=\widehat{ECA}\left(=\widehat{BAH}\right)\)
On the other hand, \(EC//AD\Rightarrow\widehat{ECA}=\widehat{CAD}\) (2 staggered angles)
Thus, \(\widehat{EAH}=\widehat{CAD}\left(=\widehat{ECA}\right)\) or \(\widehat{EAH}+\widehat{EAC}=\widehat{CAD}+\widehat{EAC}\) or \(\widehat{CAH}=\widehat{DAE}\)
ADCE is a parallelogram, therefore, \(\widehat{DAE}=\widehat{DCE}\), so, \(\widehat{CAH}=\widehat{DCE}\left(=\widehat{DAE}\right)\) or \(\widehat{CAH}=\widehat{DCB}\)
We also have \(\widehat{CAH}=\widehat{B}\left(=90^o-\widehat{ACB}\right)\), so \(\widehat{B}=\widehat{DCB}\left(=\widehat{CAH}\right)\)
Consider the trapezoid ABCD (AD//BC), it has \(\widehat{B}=\widehat{DCB}\), therefore, ABCD is an isosceles trapezoid.
d) It's pretty easy! Since ABE is an isosceles triangle, \(AE=AB\). Guess what? We've already had \(AB=15cm\). So, simply, we get \(AE=15cm\) !!!
I'll let you draw the figurr by yourself.
a) There are 3 trapezoid: BDEC, BDIC and BIEC.
b) Because \(DE//BC\), \(\widehat{DIB}=\widehat{IBC}\) (2 staggered angles)
We also have \(\widehat{IBC}=\widehat{IBD}\) (because BI is the bisector of \(\widehat{ABC}\)). Thus, IBD is an isosceles triangle, which means \(ID=BD\)
Similarly, we have \(IE=CE\). Form these, we have \(ID+IE=BD+CE\) or \(DE=BD+CE\)
And that's what we have to prove!
a) Xét tam giác HBA và tam giác ABC :
góc B chung
góc BHA = góc BAC (= 90 độ)
=> Tam giác HBA đồng dạng với tam giác ABC
b) Áp dụng định lí pytago vào tam giác vuông ABC, ta được :
AB^2 + AC^2 = BC^2
=> 15^2 + 20^2 = BC^2
=> BC^2 = 625
=> BC = 25 (cm)
Vì tam giác HBA đồng dạng với tam giác ABC
=> AH/AC = AB/BC
=> AH/20 = 15/25
=> AH = 20.15/25 = 12 (cm)
No one but you draw the figure.
a) Consider the right triangle ABC, which has \(\widehat{A}=90^o\), we have \(\widehat{B}+\widehat{C}=90^o\Leftrightarrow\widehat{C}=90^o-\widehat{B}\) (1)
On the other hand, the triangle ABC has the height AH, therefore, triangle HBA is also a right triangle \(\left(\widehat{AHB}=90^o\right)\)
Thus, we have \(\widehat{BAH}+\widehat{B}=90^o\Leftrightarrow\widehat{BAH}=90^o-\widehat{B}\) (2)
From (1) and (2), we get \(\widehat{HAB}=\widehat{C}\)
Consider the 2 triangles HAB and ABC, both of these triangles are right triangles, also, \(\widehat{HAB}=\widehat{C}\). Therefore, \(\Delta HAB~\Delta ABC\left(a.a\right)\)
b) Consider the right triangle ABC \(\left(\widehat{A}=90^o\right)\). According to the Pytagorean theorem, we have \(BC^2=AB^2+AC^2\Leftrightarrow BC=\sqrt{AB^2+AC^2}\)
Because \(AB=15cm;AC=20cm\), \(BC=\sqrt{15^2+20^2}=25\left(cm\right)\)
Triangle ABC rights at A, so \(S_{ABC}=\dfrac{1}{2}AB.AC\) (3)
Also, triangle ABC has the height AH, so \(S_{ABC}=\dfrac{1}{2}AH.BC\)(4)
From (3) and (4), we have \(\dfrac{1}{2}AH.BC=\dfrac{1}{2}AB.AC\left(=S_{ABC}\right)\Leftrightarrow AH.BC=AB.AC\)\(\Leftrightarrow AH=\dfrac{AB.AC}{BC}=\dfrac{15.20}{25}=12\left(cm\right)\)
So, \(BC=25cm\) and \(AH=12cm\)
c) What is the question? I can't see it.
a) Ta có: \(Q=12x-4x^2-11=-\left(4x^2-12x+9\right)-2=-\left(2x-3\right)^2-2< 0\)
\(\Rightarrow\)ĐPCM
b) Ta có: \(\left(a^3+b^3\right)\left(a^2+b^2\right)=a^5+b^5+a^3b^2+a^2b^3=a^5+b^5+a^2b^2\left(a+b\right)\)
Mà \(ab=1\Rightarrow\left(a^3+b^3\right)\left(a^2+b^2\right)=a^5+b^5+\left(a+b\right)\)
\(\Rightarrow a^5+b^5=\left(a^3+b^3\right)\left(a^2+b^2\right)-\left(a+b\right)\)
a) We have \(Q=12x-4x^2-11=-\left(4x^2-12x+9\right)-2=-\left(2x-3\right)^2-2\)Because \(-\left(2x-3\right)^2\le0\); \(-\left(2x-3\right)^2-2\le-2< 0\Leftrightarrow Q< 0\)
And that's the thing we have to prove.
b) Just expand the polynomial on the right side of the equality:
We have \(R=\left(a^3+b^3\right)\left(a^2+b^2\right)-\left(a+b\right)\) \(=a^5+b^5+a^3b^2+a^2b^3-\left(a+b\right)\)\(=a^5+b^5+a^2b^2\left(a+b\right)-\left(a+b\right)\)
On the other hand, \(ab=1\Leftrightarrow a^2b^2=1\)
Therefore, \(R=a^5+b^5+\left(a+b\right)-\left(a+b\right)=a^5+b^5=L\)
Thus, the quality was proved.
a/ \(x^3+y^3+z^3-3xyz=\left(x+y\right)^3+z^3-3xy\left(x+y\right)-3xyz=\left(x+y+z\right)\left[\left(x+y\right)^2-\left(x+y\right)z+z^2\right]-3xy\left(x+y+z\right)=\left(x+y+z\right)\left(x^2+2xy+y^2-xz-yz+z^2-3xy\right)=\left(x+y+z\right)\left(x^2+y^2+z^2-xy-yz-zx\right)\)\(\Rightarrowđpcm\)
b/ \(x^7+x^5+1=x^7+x^6+x^5-\left(x^6+x^5+x^4\right)+\left(x^5+x^4+x^3\right)-\left(x^3+x^2+x\right)+\left(x^2+x+1\right)=x^5\left(x^2+x+1\right)-x^4\left(x^2+x+1\right)+x^3\left(x^2+x+1\right)-x\left(x^2+x+1\right)+\left(x^2+x+1\right)=\left(x^2+x+1\right)\left(x^5-x^4+x^3-x+1\right)\left(đpcm\right)\)
\(VT=x^3+y^3+z^3=\left(x+y\right)^3+z^3-3x^2y-3xy^2=\left(x+y+z\right)\left[\left(x+y\right)^2-\left(x+y\right)z+z^2\right]-3x^2y-3xy^2-3xyz+3xyz=\left(x+y+z\right)\left(x^2+2xy+y^2-xz-yz+z^2\right)-3xy\left(x+y+z\right)+3xyz=3xyz+\left(x+y+z\right)\left(x^2+2xy+y^2-xz-yz+z^2-3xy\right)=3xyz+\left(x+y+z\right)\left(x^2+y^2+z^2-xy-yz-xz\right)=VP\left(DPCM\right)\)
gọi cạnh sân hình vuông là x đk x > 0
diện tích sân hình vuông là x2
chiều dài sân hình chữ nhật là x + 3
chiều rộng là x - 2
diện tích sân hình chữ nhật là (x+3)(x -2)
theo bài ra ta có x2 = (x+3)(x -2)
x2 = x2 - 2x + 3x - 6
x - 6 = 0
x = 6
vậy cạnh sân hình vuông là 6 m
Gọi cạnh hình vuông là \(x\) (\(x>0\))
Diện tích sân hình vuông là : \(x^2\)
Chiều dài sân hình chữ nhật là : \(x+3\) ; chiều rộng : \(x-2\)
Diện tích sân hình chữ nhật là : \(\left(x+3\right)\left(x-2\right)\)
Ta có : \(x^2=\left(x+3\right)\left(x-2\right)\)
\(\Leftrightarrow x^2=x^2-2x+3x-6\)
\(\Leftrightarrow x-6=0\Leftrightarrow x=6\)
Vậy cạnh sân hình vuông là \(6m\)
A B C D E F M N
a/
Xét tg ABE và tg CDF có
BE=FD (gt)
AB=CD (cạnh đối hbh)
\(\widehat{ABE}=\widehat{CDF}\) (góc so le trong)
=> tg ABE = tg CDF (c.g.c) => AE=CF (1)
Chứng minh tương tự ta cũng có tg ADF = tg BCE
=> AF=CE (2)
Từ (1) (2) => AECF là hbh (Tứ giác có các cặp cạnh đối bằng nhau từng đôi 1)
b/
Xét tg BCF có
BE=EF
EM//CF
=> MB=MC (trong tg đường thẳng // với 1 cạnh và đi qua trung điểm 1 cạnh thì đi qua trung điểm cạnh còn lại)
C/m tương tự khi xét tg CDE => NC=ND
c/
Ta có
\(BE=EF=FD=\dfrac{BD}{3}\Rightarrow BD=3.FE\)
Xét tg BCD có
MB=MC; NC=ND => MN là đường trung bình của tg BCD
\(\Rightarrow MN=\dfrac{BD}{2}=\dfrac{3.EF}{2}\)
\(1+8.\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)-9^8\)
\(=1+\left(3^2-1\right).\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)-9^8\)
\(=1+\left(3^4-1\right)\left(3^4+1\right)\left(3^8+1\right)-9^8\)
\(=1+\left(3^8-1\right)\left(3^8+1\right)-9^8\)
\(=1+\left(3^8\right)^2-1-9^8=\left(3^2\right)^8-9^8=9^8-9^8=0\)